2021
DOI: 10.3390/en14092675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen and Steam Equivalence Ratios on Updraft Gasification of Biomass

Abstract: Several experimental datasets available on the gasification of different lignocellulosic feedstocks were used to correlate the flow of gasifying agents with the performance of updraft gasification in an autothermic 200 kWth pilot plant. The feedstocks used included eucalyptus wood chips, torrefied eucalyptus and spruce chips, lignin rich residues from biorefined straw and reed, shells of almond and hazelnut, which were gasified in flows of air, air and steam, oxygen, oxygen and steam. Thermal profiles inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Without loss of generality, we will assume, for instance, that w=0.1 ${w}=0.1$ and o=0.3 ${o}=0.3$. For a more thorough investigation regarding the proper choice of oandw $o\,\text{and}\,{w}$, one need to introduce variables called Equivalence Ratios (ER) for both oxygen and steam [22]. Then, perform a sensitivity analysis to fetch the optimal proportions (i.e., those which lead to high hydrogen yield or low tar formation, etc.)…”
Section: Case Studiesmentioning
confidence: 99%
“…Without loss of generality, we will assume, for instance, that w=0.1 ${w}=0.1$ and o=0.3 ${o}=0.3$. For a more thorough investigation regarding the proper choice of oandw $o\,\text{and}\,{w}$, one need to introduce variables called Equivalence Ratios (ER) for both oxygen and steam [22]. Then, perform a sensitivity analysis to fetch the optimal proportions (i.e., those which lead to high hydrogen yield or low tar formation, etc.)…”
Section: Case Studiesmentioning
confidence: 99%
“…In MBG, higher steam requirements reduce superheated spots in the bed but also decrease bed permeability, while a high S/F ratio suppresses process temperature and secondary tar cracking reactions. Cerone et al [106] found that an increase in the S/F ratio resulted in a higher proportion of tar because of a decrease in average bed temperature which favoured higher tar production. It is observed that MBG requires more steam than FBG and EFG for preventing channel burning and superheated spots in the bed.…”
Section: Operational Effectsmentioning
confidence: 99%
“…Cerone et al. 106 found that an increase in the S/F ratio resulted in a higher proportion of tar because of a decrease in average bed temperature which favoured higher tar production. It is observed that MBG requires more steam than FBG and EFG for preventing channel burning and superheated spots in the bed.…”
Section: Factors Affecting Gasifier Performancementioning
confidence: 99%
“…However, too much steam in the gas generator may negatively affect energy production, as the system loses great energy on heating the steam. Excessive steam in the gas generator may also reduce the reaction temperature, thus impairing the gas quality [87].…”
Section: Effect Of Gasifying Agentmentioning
confidence: 99%